Polycyclic aromatic hydrocarbons (PAHs) in surface sediments from the intertidal zone of Bohai Bay, Northeast China: Spatial distribution, composition, sources and ecological risk assessment. Issue 1 (15th November 2016) - Qian, Xiao; Liang, Baocui; Fu, Wenjun; Liu, Xinhui; Cui, Baoshan
Abstract: Polycyclic aromatic hydrocarbons (PAHs) can enter intertidal zones by various pathways and pose potential threats to intertidal ecosystem. We investigated distribution, composition, sources and risk assessment of PAHs in intertidal surface sediments of Bohai Bay. Total PAH concentrations ranged from 37.2 ng·g − 1 to 206.6 ng·g − 1, among which high values occurred near Nanpaishuihe River Estuary and Haihe River Estuary. The composition patterns of PAHs were characterized by the predominance of 3-ring and 4-ring PAHs, and acenaphthylene was the most dominant component. Diagnostic ratios and principal component analysis have confirmed that PAH contaminants originated from mixed sources, and the major was local combustion. The mean benzo( a )pyrene equivalent concentration of total PAHs in intertidal sediments was 15.67 ng·g − 1, which was mostly contributed by seven carcinogenic PAHs. According to ecological risk assessment, negative effects related to acenaphthylene would occur occasionally in partial survey regions of the study. Graphical abstract: Highlights: Ten intertidal sediment samples were collected for investigation of PAHs. Ace could be used as a suitable indicator to estimate total PAH concentrations. PAHs originated from mixed sources, and the major was local combustion. Adverse effects related to Acy would occur occasionally in partial study regions.